2018
DOI: 10.1111/jfb.13596
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of damage to live v. euthanized Atlantic salmon Salmo salar smolts from passage through an Archimedean screw turbine

Abstract: This study assessed the usefulness of passing euthanized Atlantic salmon Salmo salar smolts through an Archimedean screw turbine to test for external damage, as compared with live, actively swimming smolts. Scale loss was the only observed effect. Severe scale loss was 5·9 times more prevalent in euthanized turbine-passed fish (45%) than the live fish (7·6%). Additionally, distinctive patterns of scale loss, consistent with grinding between the turbine helices and housing trough, were observed in 35% of euthan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Fish-friendly turbines (e.g. the Archimedes screw; Brackley et al, 2018) may also be used to combine the advantage of electricity production and a potential safe migration route, but some studies have demonstrated their low attraction (Havn et al, 2017;Piper et al, 2018;Renardy et al, 2020) or provided new insights on the fishfriendliness of Archimedes hydrodynamic screws (Pauwels et al, 2020). Another challenge is to understand the selection of a migration route by smolts when they are confronted with multiple choices, combining both safe and unsafe routes (Renardy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Fish-friendly turbines (e.g. the Archimedes screw; Brackley et al, 2018) may also be used to combine the advantage of electricity production and a potential safe migration route, but some studies have demonstrated their low attraction (Havn et al, 2017;Piper et al, 2018;Renardy et al, 2020) or provided new insights on the fishfriendliness of Archimedes hydrodynamic screws (Pauwels et al, 2020). Another challenge is to understand the selection of a migration route by smolts when they are confronted with multiple choices, combining both safe and unsafe routes (Renardy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A substantial number of fish were found with scale loss, grinding injury, bleeding, and partial or complete cuts. In a study on the River Dart, UK, it was observed that almost all fish, including eels (Anguilla anguilla), trout (Salmo trutta) and salmonids (Salmo salar), passed through the Archimedes screw either unharmed (eels) or with negligible scale loss (salmon) [7][8][9][10]. Similarly, scale loss did not differ between treatment and control groups of salmon in a study on the river Don, Scotland [10], but investigations of scale loss on euthanized individuals at the same site showed severe scale loss and distinctive patterns of scale loss due to grinding between the turbine blades and housing trough [11].…”
Section: Introductionmentioning
confidence: 99%
“…In a study on the River Dart, UK, it was observed that almost all fish, including eels (Anguilla anguilla), trout (Salmo trutta) and salmonids (Salmo salar), passed through the Archimedes screw either unharmed (eels) or with negligible scale loss (salmon) [7][8][9][10]. Similarly, scale loss did not differ between treatment and control groups of salmon in a study on the river Don, Scotland [10], but investigations of scale loss on euthanized individuals at the same site showed severe scale loss and distinctive patterns of scale loss due to grinding between the turbine blades and housing trough [11]. In addition, further studies found that fish with a body mass less than 1 kg were not injured by contact with the screw leading edge if the tip speed was less than 4.5 m/s, and the addition of a rubber leading edge further reduced injuries to larger fish at higher tip speeds [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Habitat fragmentation occurs largely as a result of anthropogenic processes, affecting both terrestrial (e.g., road construction, deforestation, agriculture) and aquatic (e.g., construction of dams, weirs, and culverts) ecosystems (Haddad et al., 2015 ; Jones et al., 2019 ). This constrains the natural movement of animals, the consequences of which range from suboptimal resource acquisition (Andren, 1994 ; Saunders et al., 1991 ) to mortality from interactions with human‐built structures (Brackley et al., 2018 ; Haigh et al., 2014 ; Thorstad et al., 2008 ). These negative consequences may be either direct (e.g., collisions with motor vehicles during road crossings, strikes from hydropower turbines) or indirect (e.g., excessive energy expenditure, increased predation).…”
Section: Introductionmentioning
confidence: 99%
“…This constrains the natural movement of animals, the consequences of which range from suboptimal resource acquisition (Andren, 1994;Saunders et al, 1991) to mortality from interactions with humanbuilt structures (Brackley et al, 2018;Haigh et al, 2014;Thorstad et al, 2008). These negative consequences may be either direct (e.g., collisions with motor vehicles during road crossings, strikes from hydropower turbines) or indirect (e.g., excessive energy expenditure, increased predation).…”
Section: Introductionmentioning
confidence: 99%